The Effect of a Rehabilitation Program on Improving Knee Joint Range of Motion in Injured Basketball Players - Kareem , Karrar; Abood , Diaa (Journal of Physical Education, 2025)
The research aimed to evaluate the physical condition of the Al-Talaba Club players in (16) matches in the Iraqi Premier League for football using the (PLAYERTEKTEAM) device, which works with global positioning technology, and to find out if there is an increase or decrease in the physical condition, or the physical performance of the players in the matches. High level, medium level, or lower, at the beginning of the second stage, and at the end of the league, The researcher concluded that there are significant differences in the variables of distance, speed distance, power plays, number of accelerations, deceleration and player load in high-level matches compared to low- or medium-level matches and in favor of high-level matches. There is a decrease in The physical performance of the variables that were measured as a result of the effect of the hot weather in Iraq on the players, especially in the matches of the seventh month, and the occurrence of a decrease in physical performance in the last match of the league for the variables of the number of acceleration and maximum deceleration, and that the tactical aspect of the team affects the results of the physical variables that were measured.